Między profesjonalizmem a służbą społeczną. Dyskusja środowiska dydaktyków historii na temat kształcenia przyszłych nauczycieli historii w Polsce po 1989 roku - Klimorowska, Małgorzata; Skórzyńska, Izabela (Biuletyn Historii Wychowania, 2019)
In the article, a postulate is put forward to train professional history teachers by taking into consideration their social service: to prepare them well for the role of guides in the world of knowledge and values while granting them more autonomy. The goal is to draw attention to the professionalism of teachers as described by Wanda Dróżka and Dorota Gołębniak: (1) “professional autonomy”; (2) “care for maintaining and developing high standards of specialist and ethical qualifications”; (3) “reflection and self-reflection”; (4) “adopting own practices in an appropriate, individual way” (5) “high prestige and a relatively good remuneration”. The defined professionalism of teachers is the basis for their autonomous, satisfying and responsible work at school and the local environment. It is a combination of a postulate of social service and competences. The article presents a discussion of historians on teachers’ education in the context of making their vocation more professional.